Free radical-scavenging activities and cytoprotective effect of polyphenol-rich ethyl acetate fraction of guava (Psidium cattleianum) leaves on H2O2-treated HepG2 cell - Mosaddik, Ashik; Moon, Jeong Yong; Lee, Sarah; Jeong, Seongweon; Kim, Jong-Chan; Ahn, Kwang Seok; Cho, Somi Kim (© 2013 Springer Link, 2016)
This article was published in Journal of the Korean Society for Applied Biological Chemistry [© 2013 Springer Link] and the definite version is available at: http://link.springer.com/article/10.1007/s13765-013-3156-z The article website is at: http://link.springer.com/journal/13765